Effect of Organizational Structure on the Performance of State Corporations in Kenya - Kenneth Riany Goga (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
The aim of this paper was to assess the influence of organization structure on the performance of state corporations in Kenya. The study adopted an exploratory survey since it sought to ascertain respondent’s perceptions on the determinants of collective bargaining agreement in a structured manner. The target population of this study included all 187 state corporations in Kenya. The unit of analysis was all the State Corporations in Kenya while the unit of observation was the Heads of Human Resources in each corporation. The study used a sample of 95 state corporations and collected primary data using a self-administered questionnaire. The data was analysed using descriptive statistics comprising of mean, standard deviations, frequency distribution, percentages, factor analysis, correlation analysis, structural equation modeling as well as regression analysis; SPSS Version 24 was used. The study established that organizational culture had a significant and positive influence on the performance of state corporations in Kenya, in that it affected the employee productivity and so the firm’s performance. The study recommended that firm leaders should embrace an effective and flexible organizational structure in order to promote employee performance.